Experimental investigation on the dissociation conditions of methane hydrate in the presence of imidazolium-based ionic liquids. (May 2015) - Sabil, Khalik M.; Nashed, Omar; Lal, Bhajan; Ismail, Lukman; Japper-Jaafar, Azuraien
Highlights: Study on thermodynamic effect of ionic liquids on methane hydrate (liquid + vapour) equilibrium line (HLVE). The performance of ionic liquid as new class of gas hydrate inhibitor is investigated. Conductivity and pH effect of ionic liquid on gas hydrate inhibition. HPμDSC measurements of methane hydrate dissociation temperature. The dissociation enthalpy of methane hydrate is calculated. Abstract: In this work, the performance of nine ionic liquids (ILs) as thermodynamic hydrate inhibitors is investigated. The dissociation temperature is determined for methane gas hydrates using a high pressure micro deferential scanning calorimeter between (3.6 and 11.2) MPa. All the aqueous IL solutions are studied at a mass fraction of 0.10. The performance of the two best ILs is further investigated at various concentrations. Electrical conductivity and pH of these aqueous IL solutions (0.10 mass fraction) are also measured. The enthalpy of gas hydrate dissociation is calculated by the Clausius–Clapeyron equation. It is found that the ILs shift the methane hydrate (liquid + vapour) equilibrium curve (HLVE) to lower temperature and higher pressure. Our results indicate 1-(2-hydroxyethyl) 3-methylimidazolium chloride is the best among the ILs studied as a thermodynamic hydrate inhibitor. A statistical analysis reveals there is a moderate correlation between electrical conductivity and the efficiency of the IL as a gas hydrate inhibitor. The average enthalpies of methane hydrate dissociation in the presence of these ILs are found to be in the range of (57.0 to 59.1) kJ ⋅ mol −1 . There is no significant difference between the dissociation enthalpy of methane hydrate either in the presence or in absence of ILs.